Pulse crops: nutrient density, affordability, and environmental impact - Drewnowski, Adam; Conrad, Zach (Frontiers in Nutrition, 2024)
Sustainable foods need to be nutrient-rich, affordable, environmentally friendly, and socially acceptable. Pulses, which include beans, lentils, chickpeas, and dried peas are a food group that can fit all those criteria. These concepts were tested serially using nutrient profiling methods that focused on protein and were extended to include food prices, greenhouse gas emissions, and energy demand. The present sustainability analyses were based on the US Department of Agriculture (USDA) nutrient composition and food prices data. Environmental impact data came from life cycle assessments (LCA). First, the USDA Protein Foods Group was disaggregated into animal and plant proteins. Plant proteins were separated into pulses, soy products, and nuts and seeds. Pulses were among the lowest-cost protein sources (per 100g and per 100 kcal) and had the lowest greenhouse gas emissions GHGE and energy demand . Pulses were among the most sustainable foods when monetary and energy costs were expressed per 50g of protein (equivalent to 100% DV). Pulses scored well on the Nutrient Rich Food (NRF9.3) nutrient profiling system and on the related Affordable Nutrition Index that assessed nutrient density per penny. As dietary guidance turns to plant-based diets, pulses need to be integrated into the global sustainability framework. Pulses are a source of low-cost plant-based protein and a variety of priority vitamins and minerals, have low carbon footprint and energy demand, and are a valued culinary ingredient across diverse regions and cultures.